The effect of team composition toward organizational performance at Universiti Teknologi Mara (UiTM) Jengka, Pahang / Nur Fasheha Ahmad Kamal - Ahmad Kamal, Nur Fasheha (Faculty of Business and Management, 2018)
The main focused for this research study was to examine the effect of team composition towards organizational performance. This study was conducted at Universiti Teknologi MARA (UiTM) in Jengka, Pahang. Basically, the team is a group of individuals which can be at least two or more individuals who communicate well and work together to accomplish the goals and objectives. In an organization, the performance of employees is the most important factor that will give an impact on organizational performance. Therefore, the researcher focused on three (3) independent variable of team composition which are teamwork, team size and team effectiveness to know the effect on the organizational performance as the dependent variable. The research method used to gain the result was correlation research by distributing a questionnaire among the employees. The sampling technique that has been used was a simple random technique with 114 respondents as the sample size. From the finding and analysis, the researcher found out that teamwork and team effectiveness have an effect on the performance of UiTM Jengka, Pahang. Meanwhile, team size did not give effect on the organizational performance. Therefore, the organization needs to focus more on this element by maintaining the positive result and improving the negative result to ensure every team in the organization can manage to achieve company objectives and goals successfully.